Faktor-Faktor Yang Ada Hubungan Dengan Pengendalian Tekanan Darah Penderita Hipertensi Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2011 Sampai Dengan Tahun 2021 - Annisa, Aqilah; Dwirosalia, Desi; Wangi, Harakati (Bosowa Medical Journal, 2024)
Controlling blood pressure in patients with hypertension is an effort to prevent blood pressure from exceeding the threshold, namely systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg. The purpose of this study was to determine the factors that have a relationship with controlling blood pressure of patients with hypertension in several locations in Indonesia for the period from 2011 to 2021. This research method is an analytical study by synthesizing the results obtained from ten scientific research journals with case-control research design. The results of the ten journals analyzed showed that the factors that were associated with controlling blood pressure in patients with hypertension in several locations in Indonesia, namely that there was a significant relationship between medication adherence, body mass index, smoking habits, habits exercise, and salt diet on blood pressure of hypertensive patients with p value <0,05. The conclusion of controlling blood pressure of hypertension sufferers in several locations in Indonesia for the period 2011 to 2021 there is a significant relationship with medication adherence, body mass index, smoking habits, exercise habits, and salt diet.